Gambaran Saturasi Oksigen dan Kadar Hemoglobin pada Pasien COVID-19 - Christofel O. Tompodung; Ivonny M. Sapulete; Damajanty H. C. Pangemanan (eBiomedik, 2022)
Abstract : Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by a virus called Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-). Oxygen saturation of COVID-19 patients below 95% can cause the body to experience a lack of oxygen, which is called Hypoxemia or Hypoxia. Below normal hemoglobin levels is a blood disorder called anemia. In studies related to low hemoglobin levels, it is said that low hemoglobin levels can make COVID-19 patients experience worse outcomes. The aims of this study is to find out the description of oxygen saturation and hemoglobin levels in COVID-19 patients at the Robert Wolter Mongisidi Hospital. The research used was descriptive retrospective with a cross sectional research design. The study was conducted by looking at the medical record data of COVID-19 patients taken at the Robert Wolter Mongisidi Hospital Manado. Based on research on 135 patients COVID- 19 are included in the inclusion criteria showed a frequency distribution by sex, male as many as 82 patients (61 %) and female 53 patients (39%). The results of normal oxygen saturation were 112 patients (83%) and the results of normal hemoglobin levels were 102 patients (76%). For oxygen saturation below 95% as many as 23 patients (17%) and low hemoglobin levels in 33 patients (24%). In conclusion, it was found that the results of the oxygen saturation and hemoglobin levels of COVID-19 patients were generally normal because the patients treated were mostly mild and moderate.Keywords: oxygen saturation; hemoglobin level; Coronavirus disease 2019 (COVID-19) Abstrak : Coronavirus Disease 2019 (COVID-19) merupakan penyakit menular diakibatkan oleh karena virus yang disebut Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-). Saturasi oksigen pasien COVID-19 di bawah 95% dapat menyebabkan tubuh mengalami kekurangan oksigen, yang disebut Hipoksemia atau Hipoksia. Kadar hemoglobin di bawah normal adalah kelainan darah yang disebut anemia. Dalam penelitian terkait rendahnya kadar hemoglobin, dikatakan bahwa kadar hemoglobin yang rendah dapat membuat pasien COVID-19 mengalami outcome yang buruk. Penelitian ini untuk mengetahui gambaran saturasi oksigen dan kadar hemoglobin pada pasien COVID-19. Metode penelitian deskriptif retrospektif dengan rancangan penelitian cross sectional. Penelitian dilakukan dengan melihat data rekam medis pasien COVID-19 yang diambil di Rumah Sakit Robert Wolter Mongisidi Manado. Berdasarkan penelitian pada 135 pasien COVID-19 yang termasuk dalam kriteria inklusi didapatkan hasil distribusi frekuensi berdasarkan jenis kelamin, laki – laki sebanyak 82 pasien (61%) dan perempuan 53 pasien (39%). Hasil saturasi oksigen normal sebanyak 112 pasien (83%) dan hasil kadar hemoglonbin normal sebanyak 102 pasien (76%). Untuk saturasi oksigen di bawah 95 % sebanyak 23 pasien (17%) dan kadar hemoglobin rendah sebanyak 33 pasien (24%). Sebagai simpulan, ditemukan hasil gambaran saturasi oksigen dan kadar hemoglobin pasien COVID-19 umumnya normal dikarenakan pasien yang dirawat paling banyak yaitu sakit ringan dan sedang.Kata kunci: Saturasi Oksigen; Kadar Hemoglobin; Coronavirus disease 2019 (COVID-19)